2020
DOI: 10.1002/ccr3.3134
|View full text |Cite
|
Sign up to set email alerts
|

Applying concurrent multidisciplinary care to gender affirmation in transgender women: A case series

Abstract: This case series presents three transgender women who underwent gender-affirming treatment with concurrent feminizing glottoplasty and penile inversion vaginoplasty. In our series, combining these into one procedure minimized anesthesia exposure and did not increase operative time, hospitalization, or complications, suggesting that they can safely combined. Gender dysphoria and vocal dysphonia are common among transgender women (TGW). 1 Gender-affirming surgical procedures can improve quality of life of transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…All 5 studies reported preintervention and postintervention outcomes on a scale of 30-120 points. Lloyd et al 33 and Casado-Morente et al 34 found that EGL improved QoL scores as measured by the TWVQ, but did not report P values. Yilmaz et al 36 and Chang et al 35 found a significant improvement in TWVQ scores postintervention.…”
Section: Validated Qol Outcomesmentioning
confidence: 95%
See 4 more Smart Citations
“…All 5 studies reported preintervention and postintervention outcomes on a scale of 30-120 points. Lloyd et al 33 and Casado-Morente et al 34 found that EGL improved QoL scores as measured by the TWVQ, but did not report P values. Yilmaz et al 36 and Chang et al 35 found a significant improvement in TWVQ scores postintervention.…”
Section: Validated Qol Outcomesmentioning
confidence: 95%
“…1). 9,12,[26][27][28][29][30][31][32][33][34][35][36][39][40][41] Of these, 2 studies assessed QoL improvements following VT without surgical intervention, 12 following EGL, 3 following LRGL, and 1 following CTA (Supplemental Table 2, Supplemental Digital Content 1, http:// links.lww.com/SCS/F497).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations